Immunological Characterization of HIV and SARS-CoV-2 Coinfected Young Individuals - Claudia Vanetti; Daria Trabattoni; Marta Stracuzzi; Antonella Amendola; Clara Fappani; Valeria Rubinacci; Claudio Fenizia; Laura Gianolio; Mara Biasin; Anna Dighera; Irma Saulle; Elisabetta Tanzi; et al. (Cells, 2021)
While the risk of SARS-CoV-2 infection and/or COVID-19 disease progression in the general population has been largely assessed, its impact on HIV-positive individuals remains unclear. We present clinical and immunological data collected in a cohort of HIV-infected young individuals during the first wave of COVID-19 pandemic. SARS-CoV-2 RNA, virus-specific antibodies, as well as the expression of factors involved in the anti-viral immune response were analyzed. Moreover, we set up an in vitro coinfection assay to study the mechanisms correlated to the coinfection process. Our results did not show any increased risk of severe COVID-19 in HIV-positive young individuals. In those subjects who contracted SARS-CoV-2 infection, an increase in IL-10 expression and production was observed. Furthermore, in the in vitro coinfection assay, we revealed a reduction in SARS-CoV-2 replication associated to an upregulation of IL-10. We speculate that IL-10 could play a crucial role in the course of SARS-CoV-2 infection in HIV-positive individuals. These results might help defining clinical management of HIV/SARS-CoV-2 co-infected young individuals, or putative indications for vaccination schedules in this population.